Sarcoma : A Multidisciplinary Approach to Treatment - Henshaw, Robert M. (Springer International Publishing : Imprint: Springer, 2017)
The purpose of this book is to define and demonstrate how a multidisciplinary team can be organized, integrated, and utilized in the care of sarcoma patients. Real world experiences related by multiple sarcoma specialists working as members of a multidisciplinary team along with specific case examples highlighting sarcomas of bone and soft tissue in children and adults are presented in a framework geared toward practicing oncologists and surgeons in order to foster the creation and development of care teams for sarcoma patients. It is explained how a truly multidisciplinary approach, with "one stop shopping," offers better standardization and delivery of care, streamlines patient education, facilitates discussions and decision making, and provides comprehensive support throughout the treatment process. All aspects of treatment are covered, from first-line treatments for different tumor types through to salvage therapy and the development of novel investigational agents. This book will be of benefit to all members of the medical community who have a role to play in the care of these complex patients, including therapists, nurses, mid-level practitioners, primary care doctors, and subspecialists. .
Keywords: Medicine.; Radiotherapy.; Oncology.; Surgery.; elektronické knihy; electronic books